Ultrasound-induced reactive oxygen species generation and mitochondria-specific damage by sonodynamic agent/metal ion-doped mesoporous silica. Issue 68 (3rd December 2019) - Lin, Kecan; Lin, Ziguo; Li, Yujie; Zheng, Youshi; Zhang, Da
Abstract : Herein, we design tumor microenvironment specific active nano sono-chemodynamic agent for synergistic photodynamic–chemodynamic cancer therapy. Abstract : Designing tumor microenvironment (TME)-specific active nanoparticles with minimum side effects for synergistic cancer therapy has become a hot topic in the recent decades. Aiming at further enhancing the therapeutic efficacy, an in situ -induced mitochondrial dysfunction is a very promising strategy. To achieve these goals, a nano-sono-chemodynamic agent denoted as TPP-Cu@HMS, which integrated hematoporphyrin monomethyl ether (HMME), mPEG-NHS, triphenylphosphonium (TPP)-decorated mesoporous silica (MS) and coordinatively bound Cu 2+ ions for mitochondria-specific sonodynamic-chemodynamic therapy (SDT-CDT) of cancer, was designed. Upon the ultrasound (US) treatment, TPP-Cu@HMS can specifically target mitochondria and in situ generate 1 O2 against cancer cells. Specifically, to overcome the short lifespan of 1 O2, the released Cu 2+ ions from TPP-Cu@HMS could act as a Fenton-like agent to convert endogenous H2 O2 to ·OH in the acidic environment of cancer cells, disrupt the mitochondrial membrane potential and lead to mitochondrial disintegration, which could systematically enhance the therapeutic efficiency of SDT. Therefore, we highlight the current strategy as a promising prospect for cancer therapy.